A highly active and regioselective cannabigerolic acid synthase engineered from a promiscuous prenyltransferase NphB - Park, Ye Seop; Kim, Minju; Na, Chae Yeong; Ham, Hyeon Woo; Cho, Jun Young; Park, Boyoung; Jung, Cheulhee; Park, Daechan; Yoo, Tae Hyeon (Catalysis Science and Technology, 2025)
Cannabinoids are a class of natural products originally isolated from the plant Cannabis sativa, and the demand for cannabinoid-derived compounds has continuously grown. Recombinant microorganisms harboring metabolic pathways for synthesizing these complex molecules have drawn considerable attention as alternatives to purification from the plant. NphB is a soluble aromatic prenyltransferase from Streptomyces sp. that has been shown to prenylate diverse aromatic substrates and can condense geranyl pyrophosphate (GPP) with olivetolic acid (OA) to form cannabigerolic acid (CBGA), a crucial precursor of various cannabinoids. However, the low activity and lack of regioselectivity of NphB have been a hurdle to developing efficient biological processes. Several engineered variants have been reported, but their catalytic properties still need further improvement for application in commercial production. We identified a critical residue (S214) for interaction with OA by characterizing a small library of NphB. The modeled structure docked with OA suggested two additional positions (A232 and Y288) for further engineering of the binding pocket of OA. Combined with a previously reported mutation of V49W, a variant having four changes (V49W/S214H/A232S/Y288P) showed the highest kcat/Km value with OA (275.89 ± 38.248 min−1 mM−1) at least to our knowledge, which was 50 000-fold higher than that of the wild-type enzyme (0.0052 ± 0.00184 min−1 mM−1). The structural analyses using the molecular dynamics simulation indicated that the remodeled binding pocket had favorable non-covalent interactions with OA, contributing to the decreased Km value for the substrate. The purified NphB variant synthesized CBGA using OA and GPP faster than other reported enzymes, which was more evident with low concentrations of the substrates. These findings suggested that the CBGA synthase engineered in this study holds promise for application in the production of various cannabinoids in microbial cell factories.
Keywords: Binding pockets; Cannabinoids; Cannabis sativa; Complex molecules; Metabolic pathways; Natural products; Prenyltransferase; Recombinant microorganism; Regio-selective; Synthases